2021
DOI: 10.3389/fphar.2021.643619
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxic Preconditioning: A Potential New Powerful Strategy for COVID-19 Rehabilitation

Abstract: COVID-19 is a highly infectious respiratory virus, which can proliferate by invading the ACE2 receptor of host cells. Clinical studies have found that the virus can cause dyspnea, pneumonia and other cardiopulmonary system damage. In severe cases, it can lead to respiratory failure and even death. Although there are currently no effective drugs or vaccines for the prevention and treatment of COVID-19, the patient’s prognosis recovery can be effectively improved by ameliorating the dysfunction of the respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Additionally, HIF-1α and β heterodimers promote cell survival, glycolysis, and angiogenesis, and have been reported dysfunctional in people with type 2 diabetes ( 133 ) and cancer ( 134 ) making people with other comorbidities more susceptible to COVID-19 infection. In addition to the obese, and the elderly, and those with comorbidities who are more susceptible, the HIF-1α gene has been reported to be activated in patients who have survived COVID-19 infections ( 135 ). Research has shown that HIF-1α increases the glycolytic metabolic enzyme pyruvate dehydrogenase kinase 1(PDK1) which reduces nutrition in the brain in the long term, affecting neurotransmitters.…”
Section: Populations With Imbalanced Th1/th2 Are Among the Most Susceptible To Become Infected By Covid 19mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, HIF-1α and β heterodimers promote cell survival, glycolysis, and angiogenesis, and have been reported dysfunctional in people with type 2 diabetes ( 133 ) and cancer ( 134 ) making people with other comorbidities more susceptible to COVID-19 infection. In addition to the obese, and the elderly, and those with comorbidities who are more susceptible, the HIF-1α gene has been reported to be activated in patients who have survived COVID-19 infections ( 135 ). Research has shown that HIF-1α increases the glycolytic metabolic enzyme pyruvate dehydrogenase kinase 1(PDK1) which reduces nutrition in the brain in the long term, affecting neurotransmitters.…”
Section: Populations With Imbalanced Th1/th2 Are Among the Most Susceptible To Become Infected By Covid 19mentioning
confidence: 99%
“…Additionally, activated HIF-1α may activate the peroxisome proliferator-activated receptor-gamma coactivator (PGC-1)-SIRT1/adenosine monophosphate-activated protein kinase (AMPK) pathway and inhibit the endothelin 1(ET-1) pathway. These factors can help reverse the virus induced cardiopulmonary hemodynamic disorder and endothelial dysfunction ( 135 ). A study suggests combined intermittent exercise with hypoxia enhanced glucose disposal and improved insulin resistance post-exercise was beneficial in the treatment of type 2 diabetes ( 138 ).…”
Section: Populations With Imbalanced Th1/th2 Are Among the Most Susceptible To Become Infected By Covid 19mentioning
confidence: 99%
“…Mild hypoxic preconditioning has become a novel therapeutic target in the treatment of hypertension [ 108 ], myocardial infarction [ 109 ], cerebral ischemia [ 110 ], and depression [ 111 ]. It is even proposed as a potential application for patients with COVID-19 [ 112 ]. Hypoxia induces neuroprotection by reducing energy consumption [ 113 ] and prevents amyloid β accumulation in AD mice [ 114 ].…”
Section: Cellular Mechanisms To Cope With the Energy Crisismentioning
confidence: 99%
“…Promising preliminary results of hypoxia exposure in animal model studies suggest that these interventions could be of great interest in treating anxiety disorders [22]. However, despite recent studies suggesting intermittent hypoxic preconditioning as a powerful strategy for COVID-19 rehabilitation [23], to our knowledge, there is no research in the scientific literature that has studied the effects of this novel therapeutic strategy on mental health parameters of adults who have recovered from COVID-19. Thus, this study aimed to investigate the effects of different protocols of moderate-intensity intermittent hypoxic training in adults who have recovered from COVID-19 on QoL and the state of their mental health.…”
Section: Introductionmentioning
confidence: 99%